2018
DOI: 10.24869/psyd.2018.41
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Repetitive Transcranial Magnetic Stimulation Using an H1-Coil or Figure-8-Coil in the Treatment of Unipolar Major Depressive Disorder: A Study Protocol for a Randomized Controlled Trial

Abstract: Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive technique with few side effects that has been reported to be effective in the treatment of major depressive disorder (MDD). At present, no randomized controlled trials (RCT) have compared the efficacy and safety of rTMS delivered by the figure-8-coil and the H1-coil. We describe an industry-independent, randomized, controlled, single-blinded, single-center study protocol assessing the differences in efficacy and safety of rTMS for patients di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
1
0
Order By: Relevance
“…In recent years, researchers have found that rTMS has an advantage of improving sleep quality, optimizing sleep structure, and maintaining therapeutic efficacy over pharmacological treatments and cognitive behavioral interventions (Aleman, ). rTMS is particularly safe for the treatment of pregnant and lactating women, the elderly, and other special populations with insomnia (Felipe & Ferrão, ; Filipčić et al, ). However, the optimal rTMS parameters have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, researchers have found that rTMS has an advantage of improving sleep quality, optimizing sleep structure, and maintaining therapeutic efficacy over pharmacological treatments and cognitive behavioral interventions (Aleman, ). rTMS is particularly safe for the treatment of pregnant and lactating women, the elderly, and other special populations with insomnia (Felipe & Ferrão, ; Filipčić et al, ). However, the optimal rTMS parameters have not yet been determined.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the therapeutic impact of DTMS persisted throughout the 16-wk maintenance phase, proving to be advantageous for patients who had previously shown no response to alternative treatments[ 15 ]. The study findings revealed a remission rate of 60% [95% confidence interval (95%CI): 48%-71%] in the DTMS group, whereas the remission rate for rTMS with conventional figure-of-eight coils was 43% (95%CI: 31%-55%)(Table 1 )[ 16 - 22 ]. In a meta-analysis conducted in 2019, it was observed that the DTMS group exhibited a response rate of 47.8%, whereas the sham group demonstrated a response rate of 25.6%.…”
Section: Dtms In Psychiatric Disordersmentioning
confidence: 99%